Franklin fibs - Bourgeois, Paulette; Clark, Brenda (New York : Scholastic, 1992)
Franklin, a turtle, says he can swallow seventy-six flies in the blink of an eye. Then he is asked to prove it. Franklin learns it is better to tell the truth.
2.5
K-3
K-3
Keywords: Truthfulness and falsehood -- Fiction; Turtles -- Fiction; Truthfulness and falsehood -- Fiction; Turtles -- Fiction